2013
DOI: 10.5812/ircmj.5044
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of sabA Gene in Helicobacter pylori Strains Isolated From Patients in Tehran, Iran

Abstract: Background:The importance of sialic acid binding adhesin (sabA) as a new outer membrane protein in gastroduodenal diseases has been recognized. The prevalence rate of sabA gene varies in different geographic areas. Objectives: The aim of this study was to determine the frequency of sabA gene in Helicobacter pylori (H. pylori) strains isolated from different clinical outcomes in Tehran, Iran. Patients and Methods:The study included 120 patients with dyspeptic symptoms admitted to the endoscopy suite of gastroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
(17 reference statements)
4
13
0
Order By: Relevance
“…In three previous studies from Iran, the frequency of sabA was reported as 86.6%, 83.6%, and 100%, respectively, with no association with the severity of clinical outcomes (32)(33)(34), and this was in line with the current findings and another study from Japan (29). In comparison with the above-mentioned studies from different countries, the current results showed a considerably lower rate of sabA.…”
Section: Discussionsupporting
confidence: 88%
“…In three previous studies from Iran, the frequency of sabA was reported as 86.6%, 83.6%, and 100%, respectively, with no association with the severity of clinical outcomes (32)(33)(34), and this was in line with the current findings and another study from Japan (29). In comparison with the above-mentioned studies from different countries, the current results showed a considerably lower rate of sabA.…”
Section: Discussionsupporting
confidence: 88%
“…(mousavi, 2007) Finally in the year 1940 the fine art faculty was established, which was the first state school at high education level started activity. (Pakbaz, 2002) In respect and by the passage of time the attention to issues and the necessity of action <ministry of education, religious contribution, and fine arts industries>, <beautiful arts general office> and <culture and art ministry> the Pahlavi era changed the art into a planned and possessing a responsible foundation. there were two contrastive tendencies existed during the official art of the Reza Shah art era.…”
Section: Education and Its Role In Boosting Up The Role Of Womenmentioning
confidence: 99%
“…Eclectic sculpture and architecture-the installment of the stature in urban settings-and attention to the pre-Islamic art era were also in fashion at that time and by the dismissal of the Reza Shah a new era of art was set on. (Pakbaz, 2002) Almost 70 years after the modernism movement in the west its reflections reached Iran and provided a chance for renovation in art areas. So that <open minded people" excitedly were in search of new ways, and their tempted curiosity, moved them towards trying different methods from impressionism to cubism, from surrealist fantasies up to imaginary formation. "…”
Section: Education and Its Role In Boosting Up The Role Of Womenmentioning
confidence: 99%
“…6 SabA binds to carbohydrates and has an important role in initial colonization of H. pylori. 7 Previous studies reported that presence of these factors is associated with the development of gastric cancer, 7 so these molecules influence the severity of inflammation and disease outcome. 8 However, the association between these factors and clinical outcomes has not exactly been determined, and the prevalence of the H. pylori babA2 and sabA genotypes has not yet been determined in Tabriz, Iran.…”
mentioning
confidence: 99%
“…6 A study in Tehran, Iran, showed sabA presences in 86.7% with gastric ulcer, and in 83.3% with gastritis and duodenal ulcer. 7 It has been proposed that sabA-positive status is negatively associated with ulcer diseases. We also found that the sabA status was related to clinical outcome in this area and the sabA gene was significantly associated with the presence of non-ulcer diseases (P = 0.005).…”
mentioning
confidence: 99%